New records of Geastraceae Corda from Northeast Brazil - Leite, Anileide G.; Baseia, Iuri Goulart (SITIENTIBUS série Ciências Biológicas, 2007)
The present study deals with the occurrence of Geastraceae from Atlantic Rainforest and Caatinga biomes in the region encompassed by the states of Rio Grande do Norte and Pernambuco. Four species have been identified: Geastrum saccatum, G. schweinitzii, G. triplex and Myriostoma coliforme, all of them representing new records from Rio Grande do Norte. The material collected was added to the herbarium URM and UFRN-fungi. Descriptions of macro and microscopic features are given, including taxonomic and ecological comments.